What Should Teacher and Student Know in the Teaching and Learning of EMP (English for Medical Purposes)? (NOBEL: Journal of Literature and Language Teaching, 2013)
EMP (English for Medical Purpose) is a part of ESP (English for Specific Purpose). It is highly needed for students having medical background since ESP has absolute characteristics as follows: (1) ESP is defined to meet specific needs of the learner, (2) ESP makes use of underlying methodology and activities of the discipline it serves, (3) ESP is centered on the language appropriate to these activities in terms of grammar, lexis, register, study skill, discourse and genre (Brunton, 2009) and it is usually designed for adult learners at an intermediate or advanced level ( Daiva CivilkienÄ—, 2008).